Genomic Multiplication and Drug Efflux Influence Ketoconazole Resistance in Malassezia restricta - Park, Minji; Cho, Yong-Joon; Lee, Yang Won; Jung, Won Hee (Frontiers in Cellular and Infection Microbiology, 2020)
Malassezia restricta is an opportunistic fungal pathogen on human skin; it is associated with various skin diseases, including seborrheic dermatitis and dandruff, which are usually treated using ketoconazole. In this study, we clinically isolated ketoconazole-resistant M. restricta strains (KCTC 27529 and KCTC 27550) from patients with dandruff. To understand the mechanisms of ketoconazole resistance in the isolates, their genomes were sequenced and compared with the susceptible reference strain M. restricta KCTC 27527. Using comparative genome analysis, we identified tandem multiplications of the genomic loci containing ATM1 and ERG11 homologs in M. restricta KCTC 27529 and KCTC 27550, respectively. Additionally, we found that the copy number increase of ATM1 and ERG11 is reflected in the increased expression of these genes; moreover, we observed that overexpression of these homologs caused ketoconazole resistance in a genetically tractable fungal pathogen, Cryptococcus neoformans. In addition to tandem multiplications of the genomic region containing the ATM1 homolog, the PDR5 homolog, which encodes the drug efflux pump protein was upregulated in M. restricta KCTC 27529 compared to the reference strain. Biochemical analysis confirmed that drug efflux was highly activated in M. restricta KCTC 27529, implying that upregulation of the PDR5 homolog may also contribute to ketoconazole resistance in the strain. Overall, our results suggest that multiplication of the genomic loci encoding genes involved in ergosterol synthesis, mitochondrial iron metabolism and oxidative stress response and overexpression of the drug efflux pumps are the mechanisms underlying ketoconazole resistance in M. restricta.